Ektrak Daging Buah Mahkota Dewa Meregenerasi Sel Pulau Langerhans Pada Tikus Putih Diabetes - Fitranto Arjadi; Mustofa Mustofa (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
In Indonesia, the increasing prevalence of diabetes mellitus is accompanied by the increasing financial burden to the patients. It is necessary to find alternative herbal treatment for diabetes, which is effective, cheap, and easy to find: the mahkota dewa. This research aims to find out the histological regeneration of Langerhans islet cells after given by flesh extract of mahkota dewa.This experimental research used complete randomized design (CRD). There were 5 treatments given to the twenty five mice; the negative control group (the normal one), the positive control (male white mice (Rattus norvegicus which were made diabetic by administering injection of 70 mg/kg of body mass of diabetogenic alloxan), the group of diabetic male white mice given 3, 6 and 9 grams/day/200 bodyweights), then were measured glucose in blood at 0, 1st and 4th week and counted Langerhans islet cells every 5 overviews.Statistically results showed that flesh extracts of mahkota dewa can decreased glucose in diabetic mice (r=0,75) with contribute 56,89% in decreasing, regenerated Langerhans islet cells of pankreas Fcount(17,558)>Ftab(2,870) with the highest increasing is 3,84 amount and started with 3grams/day/200 bodyweights doses, and the best effectiveness in regenerating was 11,81% consentration or 0,1181grams/day (6.56 grams/day in human).